Analisis Pengaruh Good Corporate Governance, Corporate Social Responsibility dan Ukuran Perusahaan Terhadap Nilai Perusahaan (Studi Pada Perusahaan Perbankan Di Bursa Efek Indonesia) - Musfialdy Musfialdy (PEKBIS, 2019)
The aim of this research is to analysis the effect of Good Corporate Governance,Corporate Social Responsibility and Firm Size toward Firm Value in Indonesia StockExchange Period 2013-2015. Population on this research includes bankingcompanies in Indonesia Stock Exchange Period 2013-2015. This research usedpurposived sampling as its sampling techniques. This research used secondarydata. Data collection technique of this research used was documentation method.Analysis method that used of this research was multiple regression analysis. Basedon the hypothesis testings, this research concludes: 1) Managerial ownership has nosignificant effect on Firm Value. This indicates that the growth of the number ofshares owned by the management company have no significant impact on the Firm.2) Corporate social responsibility has no significant effect on Corporate Value. Thisindicates that aspects of CSR activities have no significant impact on the FirmValue. 3) Firm size has a significant negative effect on Corporate Value. Thisindicates that the growth of total assets owned by the company has a verysignificant impact on the high value of the company in the eyes of investors.